Recent advances in the analysis of competition policy and regulation - Harrington, Joseph E. (Edward Elgar Publishing Ltd. CheltenhamGB, 2012)
Analyses various aspects oc competition policy. Addresses issues concerning the implications of switching costs and network effects in competition policy, the effects of leniency programmes, the identification of maverick firms. Offers a brief review of online searches and their relation to competition policy issues.